Brand Value and Tourists’ Satisfaction in Lombok Indonesia as a Halal Tourism Destination - Muhamad Yusup; Maimunah Johari; Riduan Mas'ud (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Since 2015, the Ministry of Tourism and Creative Economy of the Republic of Indonesia has appointed Lombok of West Nusa Tenggara as a halal tourism destination. Because of its natural beauty, which is comparable to that of Bali, the majority of the population is Muslim, and the island has a distinct religious culture and history, Lombok has a lot of promise in promoting halal tourism in Indonesia. This study intends to elucidate the relationship between destination brand awareness, brand image, brand quality, and destination brand value in increasing the destination brand satisfaction of tourists visiting Lombok. This study proposes a new model and clarifies the concept of a new indicator on the variable of destination brand value. Upon analysis of structural equation modeling (SEM) using convenience sampling employing WarpPLS software to 250 respondents, it was proven that the research model was accepted with a coefficient of determination (R2) of 86.6%. The proposed model shows destination brand value to be a determinant of tourists’ satisfaction. The model also proves that indicators of convenience, reasonable cost, fun, and getting benefits make a positive contribution to brand value destinations. This study offers practical implication that tourism managers should pay attention to and improve brand image, which currently has little impact on destination brand value, by building brand popularity and competitive advantages.